Bismuth‐doped compound germanate glass microsphere lasing in the near‐infrared region. Issue 1 (6th September 2019) - Liang, Haidong; Wang, Xin; Yu, Jibo; Yang, Wenlei; Lewis, Elfed; Wang, Pengfei
Abstract: A bismuth‐doped compound glass‐based microsphere laser is reported. The fluorescence luminescence of the bismuth‐doped compound glass is measured over an ultra‐broad wavelength range of 1100 to 1700 nm excited using an 808 nm pumping source. The glass microsphere was fabricated using a CO2 laser heating the fiber near its melting temperature, and when coupled with the tapered silica fiber, yielded the 1310 nm laser emission pumped using an 808 nm laser diode. The 245 μW––low absorbed pumping threshold of the microsphere, 3.57 μW laser output and the tunable multiple wavelength emissions demonstrate great potential applications for use in near infrared broadband fiber amplifiers and tunable lasers.